Exploring the mediating effect of brand relationship quality in the service brand equity and brand resonance linkage - Sharizal Hashim; Norjaya Mohd Yasin (Penerbit Universiti Kebangsaan Malaysia, 2012)

(untitled)
This study attempts to explore the mediating role of brand relationship quality in predicting the effects of service brand equity towards brand resonance in Malaysia's mobile communication service. The reliability test on all these constructs produce satisfactory reliability coefficients. Correlation analysis is conducted and the results indicate that there are positive and significant relationships among the constructs. Then, Sobel s' test is used to investigate the occurrence of mediation in the study. The result shows service brand equity and brand resonance is significantly related through the mediating effect ofbrand relationship quality. This is in line with the assumption of social exchange theory that anticipates the central discipline of human behaviour is about the quality of the relationship that emerges in the exchange process. Therefore, it is hoped that the findings and discussion will contribute to the theory of consumer behavior, branding and relationship marketing, as well as to offer insightful knowledge for practical consideration.